Demonetization and digital payments in India: perception and reality. Issue 4 (23rd February 2021) - Chakrabarty, Manisha; Jha, Ashutosh; Ray, Partha
ABSTRACT: In the context of the demonetization experiment of November 2016 in the Indian economy, this paper aims at looking into its impact on digital payments. Using the major digital payment modes and following the methodology of time-series outlier detection proposed by Chen and Liu (1993), the impacts are found to be mostly transitory in nature.